Analyzing the Effectiveness of Marketing Mix Strategies in Nestlé Malaysia - Tan Lay Hong; Kai Xin Chan; Yuan Yee Chan; Jin Ye Cha; Yan Kang Chan; Arnav Kumar; Adnan Ahmed; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
NESTLÉ MALAYSIA is one of the leading companies in the FNB market in Malaysia where they delivered their good products and services to earn the consumer’s trust. They have provided quality products through a vast of brands such as Nescafe, KitKat, Maggi and Milo to Malaysians. In maintaining its market stability and dominance, Nestlé has applied a vast number of marketing strategies which is the 4Ps elements (Products, Price, Place, Promotion) to enhance consumer satisfaction. The purpose of this study is to analyze the effectiveness of these marketing elements (4Ps) and how they affect Nestlé Malaysia’s customer’s satisfaction. We had designed an online survey through Google Forms and a total of 200 respondents have participated. Price, place, and promotion significantly impact customer satisfaction, while the product element does not. This study contributes to marketing theory by providing a better understanding of consumer behaviour in the Malaysian context and by discussing how the marketing mix elements (4Ps) directly influence customer satisfaction toward Nestlé Malaysia.